HUMAN RIGHTS AND FREEDOMS IN THE CONTEXT OF AI, GLOBALISATION AND THE IDEOLOGY OF TRANSHUMANIS - Marius ANDREESCU; Andra PURAN (Challenges of the Knowledge Society)
Artificial intelligence, globalisation and the ideology of transhumanism are contemporary realities that propose a new conception of man, his social status, likely to affect the fundamental rights and freedoms enshrined in constitutions and laws. In this study we will present the content, definitions and meanings of globalisation, AI and the ideology of transhumanism, whereby the social status of man, his existence are subordinated to technology. In this context, we will insist on the risks and vulnerabilities that the new contemporary realities present for humans. We will refer to the legal means of guaranteeing human rights and to normative regulations regarding the use of AI in the context of world globalisation and the proliferation of the ideology of transhumanism.